Advances in Urban Groundwater and Sustainable Water Resources Management and Planning - Chaminé, Helder I.; Afonso, Maria José; Barbieri, Maurizio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In nature, urban groundwater results in multiple processes, including climatic, geological, geomorphological, geochemical, ecotoxicological, and hydraulic processes, in addition to sanitation, all of which sustain varied ecological services. Urban development profoundly impacts hydrological systems, particularly in the invisible component of the water cycle, the groundwater. That impact was perceived a considerable while in the past, and the initial focus was drawn to societal roles in the development of urbanisation and the consequent contamination and pollution of hydrosystems. Additional issues in sustainable water resource management and hydrological cycle comprehension are added by urbanisation. The Special Issue highlights the presentation and discussion of model urban studies and reflections that describe the current state-of-the-art methods on challenges and emerging fields related to the mapping, characterisation, assessment, mitigation, and protection of sustainable groundwater systems in peri-urban and urban areas. In the current year, 2022, World Water Day was dedicated to groundwater, and the process of making the invisible visible. This Special Issue offers a set of papers that promote reflections, methodologies, and learned studies on the importance of fresh water in urban areas.